2018
DOI: 10.1155/2018/6085961
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Ultrasonography Assessment of Functional Magnetic Stimulation on the Effect of Glenohumeral Subluxation in Acute Poststroke Hemiplegic Patients

Abstract: Background Glenohumeral subluxation (GHS) is common in patients with acute hemiplegia caused by stroke. GHS and upper limb function are closely related. Objective Using musculoskeletal ultrasonography (MSUS) to objectively evaluate the efficacy of functional magnetic stimulation (FMS) in the treatment of GHS in acute hemiplegic patients after stroke. Methods The study used prospective case control study. Stroke patients with GHS were recruited and assigned to control group and FMS group. Control group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…GHS was assessed clinically using a linear measure of fingerbreadths between the acromion and the humeral head [26]. AHD has been studied in patients with rotator cuff disorder using radiograph plain films, magnetic resonance imaging, and musculoskeletal ultrasonography [4,5,27]. With respect to the reliability of radiological methods for measuring AHD in rotator cuff tendinopathy, a systematic review found strong evidence on the reliability of ultrasound, with moderate evidence on MRI and CT measures and conflicting evidence on radiographic methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GHS was assessed clinically using a linear measure of fingerbreadths between the acromion and the humeral head [26]. AHD has been studied in patients with rotator cuff disorder using radiograph plain films, magnetic resonance imaging, and musculoskeletal ultrasonography [4,5,27]. With respect to the reliability of radiological methods for measuring AHD in rotator cuff tendinopathy, a systematic review found strong evidence on the reliability of ultrasound, with moderate evidence on MRI and CT measures and conflicting evidence on radiographic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although GHS is not typically accompanied by pain initially, as the patient continues in the flaccid stage or with injuries in soft tissues, pain may appear over an area half to two-finger widths at the shoulder joint [3]. Yang et al treated such patients with hemiplegic stroke using magnetic stimulation and found a significant drop in the bilateral differences of acromiohumeral distance (AHD) (t = 8.375, P <0.01) [4]. In a recent study on functional electrical stimulation for treating shoulder pain in stroke patients, Karaahmet et al found a positive correlation between GHS and pain (P= 0.022) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement method of deltoid muscle thickness: When the measuring posture was 0°, 30°, or 60° abduction, the probe was vertically placed at the midpoint of the joint between the lateral acromion edge of the shoulder peak and deltoid tuberosity. The probe was moved in parallel until the thickest cross-section of the deltoid muscle was determined; the image was frozen, the distance of the thickest part of the deltoid muscle was measured twice, and the average value was obtained 8) .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Park et al 6) confirmed that the increase in the acromion nodule tuberosity (ALT) distance is highly correlated with glenohumeral subluxation (GHS). Previous studies have shown that the acromion tubercle (AGT), acromion-humeral distance (AHD), supraspinatus muscle thickness, and deltoid muscle thickness can be measured using MSUS 2,7,8) . In addition, the reliability of the ultrasound in measuring the thickness of the supraspinatus muscle in the shoulder joints of stroke patients at different abduction angles has been verified 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other radiological examinations, it shows advantages including excellent visualization of shoulder structure, lack of ionizing radiation, dynamic assessment, uncomplicated operation, and cost-effectiveness [23]. By measuring the distance between two osseous landmarks, including acromiohumeral distance (AHD) [24], acromiongreater tuberosity (AGT) [22], and acromion-lesser tuberosity (ALT) [24,25], musculoskeletal ultrasonography can accurately compute the degree of subluxation in multidimensions [25].…”
Section: Introductionmentioning
confidence: 99%